DIGITAL PR CAMPAIGN ACTIVATION STRATEGY FOR LITTLE CONTRAST COFFEE SHOP ON INSTAGRAM - Yogascitra Naufal; Witri Cahyati; Widyapuri Prasastiningtyas; Hetti Herawati; Mochamad Al-Faiz (PT Altin Riset Publishing, 2026)
This study aims to analyze the implementation and planning of digital public relations campaigns implemented by Little Contrast coffee shop through the Instagram social media platform in facing the dynamics of the digital era. The method used is a case study with a qualitative approach, including observation of the types of content uploaded on Instagram social media, interviews with the Little Contrast team, and analysis of public relations campaigns conducted by the Little Contrast team to understand how public relations campaign strategies are developed and implemented. The results of the study indicate that the activation of this digital campaign is a strategy to create brand trust and brand awareness to the audience by using the eWOM strategy that introduces products through soft selling testimonials from repost stories on Instagram. Repost stories are part of the content marketing matrix with the inspire type which aims to increase awareness from the audience. By implementing digital campaign activation, Little Contrast can create content that supports the #RASAUNTUKSEMUA campaign, the type of content often used in this campaign is the content marketing matrix with the entertain and inspire types, which aim to get closer to the audience emotionally, so that the communication desired by the brand to the audience can be accepted and the audience is aware of the unique value proposition from Little Contrast.